2016
DOI: 10.1159/000446566
|View full text |Cite
|
Sign up to set email alerts
|

Serum Pentraxin 3 Fragment as a Noninvasive Marker of Nonalcoholic Fatty Liver Disease in Obese Children and Adolescents

Abstract: Background/Aims: It was suggested that serum pentraxin 3 (PTX3) levels could differentiate obese children with nonalcoholic steatohepatitis (NASH) from those with simple steatosis. Thus, we aimed to evaluate the clinical utility of serum PTX3 fragment levels in the diagnosis of NASH and the assessment of its severity in obese children with suspected nonalcoholic fatty liver disease (NAFLD). Methods: Fifty obese children were compared to 25 matched controls. All were subjected to history taking, anthropometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Our results were concomitant with previous studies. the study of Boga et al (2015) demonstrated that markedly higher PTX3 levels in NAFLD patients compared with controls, Hamza et al (2016) showed increased PTX3 in patient with NAFLD, and Afifi et al (2018) notified that serum PTX3 level was higher in NAFLD group than control group.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were concomitant with previous studies. the study of Boga et al (2015) demonstrated that markedly higher PTX3 levels in NAFLD patients compared with controls, Hamza et al (2016) showed increased PTX3 in patient with NAFLD, and Afifi et al (2018) notified that serum PTX3 level was higher in NAFLD group than control group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PTX-3 is important for diagnosing liver disease. According to some studies, PTX-3 can be used as an inflammatory marker for the prognosis of patients with hepatic cirrhosis [ 30 ]; serum PTX-3 expression markedly increases in adult NASH patients; thus, PTX-3 can be used as a biomarker for the differential diagnosis of NASH and help evaluate the severity of liver fibrosis in patients with NASH [ 12 , 31 ]. However, other studies have concluded that PTX-3 has no value in the diagnosis of NAFLD or the differential diagnosis of NASH [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disease Markers used as a biomarker for the differential diagnosis of NASH and help evaluate the severity of liver fibrosis in patients with NASH [12,31]. However, other studies have concluded that PTX-3 has no value in the diagnosis of NAFLD or the differential diagnosis of NASH [32].…”
mentioning
confidence: 99%
“…In addition, the positive correlation between plasma PTX3 levels with NAFLD activity score, fibrosis stage, and steatosis grade has been described in adults [ 23 ]. Moreover, it has also been shown that, in adolescents, PTX3 levels increased progressively with the severity of the fatty liver [ 24 ]. It should also be noted that meta-analysis of 17 studies including 2715 women diagnosed with PCOS and NAFLD and 2619 with NAFL revealed that risk of NAFLD development is higher in PCOS, and this risk is independent of obesity (diagnosed based on BMI) and may be a result of hyperandrogenism [ 25 ].…”
Section: Discussionmentioning
confidence: 99%